KINERJA PEKERJA SOSIAL DALAM MENANGANI PENYANDANG DISABILITAS INTELEKTUAL DI PANTI SOSIAL BINA GRAHITA (PSBG) NIPOTOWE PALU - Handayani, Sri (Katalogis, 2018)
This study aims to analyze the performance of social workers in dealing with intellectual disability in Bina Grahita Social Institution (PSBG) Nipotowe Palu. This research uses qualitative method. Research location at Bina Grahita Social Institution (PSBG) Nipotowe Palu. Selection of informants using Purposive is a technique of determining informants with certain considerations by setting 5 informants. Data were collected through observation techniques, interviews, and documentation. In this research, the researcher uses Millennen Milles Interpretation Analysis technique. This analytical approach technique to elicit what it means or the meaning of the problem, case, circumstance or situation under study. Result of research is social worker performance in handling intellectual disability in Bina Grahita Social Institution (PSBG) Nipotowe Palu with indicator 1). Ability. The ability of social workers at Bina Grahita Social Institution (PSBG) Nipotowe Palu has been met with a good look at the intellectual and physical abilities. 2). The motivation of social worker in Bina Grahita Social Institution (PSBG) Nipotowe Palu has not been fulfilled, this is because of the unmet needs of social workers. 3). The desire of the social worker at Bina Grahita Social Institution (PSBG) Nipotowe Palu has not been fulfilled.